2016
DOI: 10.1038/leu.2016.303
|View full text |Cite|
|
Sign up to set email alerts
|

A clinical trial for patients with acute myeloid leukemia or myelodysplastic syndromes not eligible for standard clinical trials

Abstract: Most clinical trials exclude patients with poor performance or comorbidities. To study whether patients with these characteristics can be treated within a clinical trial, we conducted a study for patients with acute myeloid leukemia (AML) or myelodysplastic syndromes (MDS) with poor performance, organ dysfunction or comorbidities. Primary endpoint was 60-day survival. Study included stopping rules for survival and response. Treatment consisted on a combination of azacitidine and vorinostat. Thirty patients (16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…Because the HMAs are the standard of care in front line higher risk MDS, a number of studies are being conducted to test combinations. Agents used in combinations include the histone deacetylase inhibitors such as pracinostat, vorinostat and panobinostat and lenalidomide . So far none of these combinations has been shown to be superior to single agent HMA.…”
Section: Risk Adapted Therapymentioning
confidence: 99%
“…Because the HMAs are the standard of care in front line higher risk MDS, a number of studies are being conducted to test combinations. Agents used in combinations include the histone deacetylase inhibitors such as pracinostat, vorinostat and panobinostat and lenalidomide . So far none of these combinations has been shown to be superior to single agent HMA.…”
Section: Risk Adapted Therapymentioning
confidence: 99%
“…48 One recent analysis of randomized trials in patients with hematologic malignancies published in a high-impact journal found that there was no association between known drug side effects and eligibility criteria, nor between eligibility criteria and adverse events actually observed in those trials. 50 In this study, the main adverse events observed were grade 1 to 2 gastrointestinal side effects and stopping rules for survival, response, and toxicity were not reached. 50 In this study, the main adverse events observed were grade 1 to 2 gastrointestinal side effects and stopping rules for survival, response, and toxicity were not reached.…”
Section: Many Patients Treated With Hma Monotherapy Do Not Derive Anymentioning
confidence: 67%
“…49 A recent clinical trial of azacitidine plus vorinostat that included patients with MDS and AML with poor performance status, serious comorbidities, or organ dysfunction confirmed the feasibility and safety of treating this subgroup of patients in a clinical trial. 50,51 These results argue for a relaxation of inclusion criteria to offer participation in clinical trials to more patients with MDS, especially for more advanced clinical trials that accrue in community practices. A performance score of 3, a creatinine or bilirubin concentration of 2 mg/dL, the presence of another malignancy, and an Adult Comorbidity Evaluation-27 (ACE-27) index score of 2 or 3 did not appear to adversely affect 60-day survival, OS, or event-free survival.…”
Section: Many Patients Treated With Hma Monotherapy Do Not Derive Anymentioning
confidence: 99%
See 1 more Smart Citation
“…Building on these observations, Montalban-Bravo et al reported an innovative phase-2 study of 109 subjects with AML or MDS ineligible for standard trials for the aforementioned reasons [20]. The study was designed to stop if the 50% 60-day survival rate for similar subjects not treated on a protocol was exceeded.…”
mentioning
confidence: 99%